シャボンダマ ニヨル ナガレ ノ カシカ ト ショウワ キチ シュウヘン ノ ユキ ノ フキダマリ - 佐藤, 稔雄; サトウ, トシオ; 半貫, 敏夫; ハンヌキ, トシオ; SATO, Toshio; HANNUKI, Toshio (国立極地研究所, 1978)
P(論文) 昭和基地に建つ高床式建物周辺に形成される雪の吹きだまりの形態を予測するため,次のような仮説を設定して風洞実験を試みた.すなわち,雪嵐の時,建物周辺で,ある特定風速を超える速度場の雪粒子は風と共に流れ,それ以下の速度場では,そこに含まれる雪粒子が地表に堆積する確率が高いと考え,建物周辺の風向,風速分布を知ることにより,吹きだまりの形態を推定しようとするものである.2次元模型による風洞実験(シャボン玉による流れの可視化および模型周辺の風速分布測定)より次の結果を得た.1)雪の吹きだまり形態は境界層の地表面摩擦速度U_*,ピロティ高さhにより変化する.2)U/U_<50>≒0.5となる高さZによる速度場区分で吹きだまり形態をほぼ推定出来る.3)ピロティを流れる流体エネルギーの指標K(式9)によっても,吹きだまり形態の変動を表現出来る.そしてこれは,U,hの関数であるから,南極基地建物計画の資料として利用出来る. The wind tunnel tests were conducted in order to predict profiles of the snowdrift formed around the buildings with the pilotis built at Syowa Station in Antarctica on the following assumptions. That is, assuming that the snow flakes in the wind velocity fields exceeding the certain mean wind velocity flow along with the wind and the other snow flakes in those fields not exceeding it tend to accumulate on the ground surface, the profiles of the snowdrift around the buildings can be predicted under the blizzard. The results of the wind tunnel tests (the flow-visualization by means of soap bubbles and the measurement of wind velocity distributions) using two-dimensional models are as follows 1) The profile of the snowdrift changes according to the surface friction velocity of the surface boundary layer U_* and the altitude of the pilotis h. 2) The profile of the snowdrift can be predicted in the division of the wind velocity field at the altitude Z satisfying in U/U_<50>≒0.5. 3) The variation of the snowdrift profile can also be expressed by the index K (eq. 9) of the fluid energy of the mean wind flowing the pilotis. Since the index K is a function of U and h, it is useful for the planning information of buildings. departmental bulletin paper